A theoretical study on the mechanism and kinetics of toxic PCDD destruction by OH radicals. (21st November 2019) - Wen, Zhengcheng; Li, Shengji; Li, Heping; Li, Yuan
The mechanism and kinetics of toxic PCDDs destruction by OH radicals is investigated in detail by employing quantum chemistry. Results show that the OH radical degrades toxic PCDDs via substituting chlorine at the 2, 3, 7, 8 positions. The kinetic parameters are calculated by adopting transition state theory. The rate constant of OCDD destruction by OH is in agreement with the experimental result, especially at 298 K. The rate constants of 2, 3, 7, 8-TCDD destruction are obviously lower than those of other toxic PCDDs. The reason is discussed by using the NBO charge analysis. Owing to the activation effect of Cl atoms at 1, 4, 6, 9 positions, C atoms at 2, 3, 7, 8 positions have more negative charge. At aromatic rings, if the carbon has more negative charge, the carbon is more easily attacked by OH and the adjacent Cl is more easily substituted.